PENGARUH FIRM SIZE, GROWTH OPPORTUNITY, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN BANK DIGITAL YANG TERDAFTAR DI BEI TAHUN 2017-2021 - Mohammad Gibran (2023)
This research is a quantitative study that aims to determine the effect of firm size, growth opportunity, and profitability on firm value at Digital Banks listed on the IDX in 2017-2021. The samples used in this study were taken using the full sampling technique, namely 11 Digital Bank companies listed on the IDX during the period 2017-2021. The analysis method in this study itself uses the Panel Data Regression Analysis Method. Based on the results of the study, it was found that (1) Decreasing or not firm size, does not affect firm value, (2) Growth Opportunity that decreases will have an effect on decreasing firm value, and vice versa, (3) Decreasing or not profitability does not have an effect on firm value.